Cue-exposure treatment influences resting-state functional connectivity: a randomized controlled fMRI study in alcohol use disorder - Farré i Colomés, Àlvar; Tan, Haoye; Gerhardt, Sarah; Gerchen, Martin Fungisai; Kirsch, Martina; Hoffmann, Sabine; Kirsch, Peter; Kiefer, Falk; Vollstädt-Klein, Sabine (Psychopharmacology, 2024)
Cue-exposure therapy (CET) consists of exposing patients to the cause of their affliction in a controlled environment and after psychological preparation. Ever since it was conceived, it has been suggested as a treatment for different types of behavioural impairments, from anxiety disorders to substance abuse. In the field of addictive behaviour, many different findings have been shown regarding the effectiveness of this therapy.
Gesehen am 21.02.2024